An Integrative Model of Competence and Comfort Factors, Affective Commitment and Organizational Citizenship Behavior of Outsourced Employees at PT. X - Cecillia Christy Pranoto (iBuss Management, 2015)
Many companies nowadays, including PT. X, is experiencing an ongoing dilemma in choosing whether or not it should do outsourcing strategy. Beside ensuring experience count and providing cost control flexibility, outsourcing strategy is bringing other consideration which is the performance of outsourced employees that probably are still in questions. Therefore, research is created to identify which elements of competence and comfort factors that actually impact the outsourced employees’ organizational citizenship behavior in order to give meaningful suggestions and recommendations for  PT. X to effectively do outsourcing strategy and still maintain its outsourced employees’ organizational citizenship behavior.This research is conducted in PT. X’s head office in Surabaya by distributing questionnaires to 139 outsourced employees. The data will be analyzed by using hierarchical multiple linear regressions analysis. The result indicates that all of the sixteen elements of competence and comfort factors simultaneously influence organizational citizenship behavior and affective commitment. Additionally, there seems to be full mediation process of affective commitment between the relationship of skill variety, task identity, transactional leadership, satisfaction with openness and organizational citizenship behavior due to similar perspective between affective commitment and organizational citizenship behavior.Keywords: Comfort Factors, Competence Factor, Affective Commitment, Organizational Citizenship Behavior.